Description of The Incidence of Back Pain After Sectio Caesarea With Spinal Anesthesia - M. Dirham, Nurul Rifah Ulmi; Triyudono, Danang; Apriliyani, Ita (Java Nursing Journal, 2024)
Background: Cesarean section (sectio caesarea) is a common surgical procedure for childbirth involving an incision in the uterine wall. Postoperative pain, particularly back pain associated with spinal anesthesia, is a prevalent concern. Previous research by Kurniawan (2022) indicated that 43.3% of patients experience moderate back pain postoperatively. However, comprehensive studies on the contributing factors to this back pain remain limited. Purpose: This study aims to analyze the incidence and determinants of back pain following cesarean section with spinal anesthesia at Siti Aminah Hospital, Bumiayu. Methods: A descriptive analytic study was conducted, employing a cross-sectional design with a survey method. The study population comprised 35 patients who underwent cesarean section with spinal anesthesia. Data were collected using structured observation sheets, focusing on variables such as patient age, needle size, anesthesia technique, patient positioning, and the severity of back pain. Findings: The majority of participants were aged 25-39 years (65.7%). A needle size of 25 gauge was used in 71.4% of cases. The median approach was the predominant anesthesia technique (82.9%), and 74.3% of procedures were performed with the patient in a sitting position. Notably, 51.4% of respondents reported mild back pain postoperatively. Conclusion: The findings suggest that patient age, needle size, anesthesia technique, and positioning during the procedure significantly influence the incidence of back pain following cesarean section with spinal anesthesia. Further research is recommended to develop strategies to minimize this complication and improve patient outcome.